Prediction of Discharge Destination Following Major Hepatectomy. Issue 11 (November 2019) - Mahvi, David A.; Pak, Linda M.; Fields, Adam C.; Urman, Richard D.; Gold, Jason S.; Whang, Edward E.
Abstract: Background: Anatomic hepatectomies can be associated with complicated post-operative recoveries, often with discharge to post-acute care facilities. This study identifies preoperative and intraoperative factors associated with increased risk for non-home discharge destination after major hepatectomy. Methods: Patients undergoing major hepatectomy were identified in the NSQIP Targeted Hepatectomy Dataset (2014–2016). Multivariable logistic regression was performed. Patients from 2014 to 2015 were used for training cohort with nomogram generation and 2016 for validation cohort. Results: Overall, 226 of 3750 patients (6.0%) were discharged to rehab, skilled care, or acute care facilities. Preoperative factors associated with non-home discharge on multivariable analysis were outside patient transfers, older age, presence of ascites, ASA physical status 3 or higher, and low preoperative hematocrit (all p  < 0.05). Intraoperative factors significantly predictive were concurrent lysis of adhesions, Pringle maneuver, and biliary reconstruction (all p  < 0.05). Predictors from testing cohort were validated in validation cohort. Nomograms based on preoperative variables alone and both preoperative and intraoperative variables were generated. Conclusion: We identify several preoperative and intraoperative factors that are associated with increased risk for non-home discharge after major hepatectomy. Preoperative anemia represents a potentially modifiable risk factor. Nomograms for preoperative planning as well as immediately following surgery were generated.